An Online Experimental Framework for Cooperative Relationships With a Real-Time Decision-Making and Rewarding Environment - Suzuki, Reiji; Ito, Momoka; Kodera, Shunnya; Nishimoto, Keita; Arita, Takaya (Frontiers in Ecology and Evolution, 2018)
This paper investigates interactions between game theoretical strategies and social relationships in real-time decision-making and rewarding environments. We propose an experimental framework based on techniques of web-based multiplayer online games for this purpose. In our framework, multiple human players, represented as particles in a two-dimensional space of social interactions, can modify their positions and game strategies for the prisoner’s dilemma in real time, and receive benefit or cost emerging from both game theoretical and social relationships with neighboring players. We report on experiments with human participants in different conditions of the payoff matrix, which reflects game structures, and the speed of each player, which reflects the ability to change her social relationship. We show that cooperative relationships emerge in real human groups regardless of experimental settings, and show their basic behavioral patterns. We further discuss relationships between behavioral characters of participants in the experiments and their psychological characters to see how their personalities can be reflected in their behavior in such a game theoretical framework, and show that a few psychological characters of participants might reflect their behavioral characters at least in part, but there were variations in these relationships between experimental groups.